In praise of the weakness of law. A response to Schauer (Società e diritti, 2019)
In this essay, the Author aim to respond to the urgings in the book “The force of Law” byFrederick Schauer breaking from the paradigm of analytical jurisprudence; insofar as theUniversity of Virginia philosopher states having found sociological bases for his ownlogical/reconstructive architecture, the Author intend to develop a critique of Schauer’s thesesthat is not merely theoretical, but sociological as well. In a nutshell whether the use of force issociologically necessary to control isolated resistance to the rules shared by the majority, or toreinforce a law, that aims to trigger necessary social change, but such a strong limitation ofhuman freedom must be justified; and this legitimacy can only derive from the need for justice.Key words: Justice, natural law, legitimization